Análisis en gestión financiera en el presupuesto del GAD Parroquial de Pimocha en los años 2019 – 2020 - Garaicoa Lara, Joselin Jeanine (2021)
The autonomous decentralized rural parish government of Pimocha, articles that include the organic code and territorial organization added to the resolutions and agreements issued by the central government, however, is an entity that is threatened due to factors such as the 56% budget cut for the year 2020 that gave rise to the lack of liquidity to face the needs, obligations and functions that this institution must fulfill, added to the arrears by the ministry of economy and finance in charge of making transfers of the amounts assigned through the budget made for each of the same periods that have caused delays in payment to suppliers, personnel acquisition of supplies, among others. Therefore, this study seeks to know the origin of the problems raised around the budget analysis in the 2019-2020 period, which will be carried out through the application of the analytical, descriptive and bibliographic research method in addition to consider the research lines of the accounting and auditing career, administrative, tax, auditing and control financial management, in turn, the survey information collection instrument will be applied that will allow collecting all those relevant criteria by those responsible to know the causes and effects that the problem has on the institution.